African Easterly Waves and Cyclonic Activity over the Eastern Atlantic: Composite and Case Studies. (22nd September 2011) - Camara, Moctar; Diedhiou, Arona; Gaye, Amadou
Abstract : This study aims to understand the main differences over the African continent and the Eastern Atlantic Ocean between African Easterly Waves (AEWs) associated with Atlantic cyclones (developing AEWs) and non-developing AEWs. A statistical study showed that most of the named cyclones generated near the West African coast have a long lifecycle and all are associated with intense AEWs. Using NCEP/NCAR reanalyses, a composite study of the characteristics of developing AEWs is carried out and compared to those of non-developing AEWs. Developing AEWs exhibit the greatest baroclinic and barotropic conversions which are known to be the main processes involved in AEWs growth suggesting that these AEWs are stronger than the non-developing ones. Moreover, the developing AEWs are characterized by the existence of a relatively more unstable environment over West Africa and the Atlantic Ocean. A case study using rawinsonde data showed that the developing AEW is associated with dynamic and thermodynamic conditions conducive for deep convection and subsequent cyclogenesis compared to the non-developing AEW case.